LOKAKARYA PENGUATAN LITERASI PROGRAM SEKOLAH PENGGERAK (PSP) SD DI KABUPATEN SIDOARJO - lestariningsih; intan bigita kusumawati; dewi sukriyah; siti nuriyatin; soffil widadah; Lailatul Mubarokah (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2023)
This article discusses the implementation of a workshop to strengthen the literacy Program Sekolah Penggerak (PSP) of primary school teachers in Sidoarjo. PSP is a government initiative to improve the quality of basic education and teacher participation is crucial to the success of the program. The workshop was designed to provide primary school teachers with an in-depth understanding of PSP concepts, objectives and implementation strategies. The method of organizing the workshop began with observation to determine the needs of the target in order to deepen the concept of literacy, then continued with the implementation of workshop activities which included presentations, group discussions, and practical simulations. Next, a questionnaire was administered to determine the interest, perceptions, attitudes and beliefs of participants towards improving literacy after participating in this activity. The evaluation results showed that the increase in teachers' understanding and involvement in PSP after attending the workshop was very positive. The results of the questionnaire on participants' perceptions of literacy improvement showed that 96% of participants had a positive perception of the workshop activities. The literacy strengthening workshop received a positive response from the participants. During the presentation of the material, participants followed with enthusiasm. This community service activity can improve teachers' understanding of literacy concepts and literacy misconceptions. participants were able to identify the potential and challenges in implementing PSP in their schools and develop strategies to improve the effectiveness of the program. With this workshop, it is hoped that the literacy of the PSP program can be improved, have a positive impact on learning at the primary level, and improve the quality of education in Sidoarjo.